Habituation of Infaq and Shodaqoh on Fridays as an Effort to Develop Students' Caring and Sharing Character (Case Study at SDN 1 Sukadana Baru) - Muhammad Khoirul Saputra; Jaenullah Jaenullah; Choirudin Choirudin (CV. Bimbingan Belajar Assyfa, 2026)
This study aims to describe the implementation of infaq and shodaqoh habituation every Friday and analyze its impact on shaping caring and sharing character of students at SDN 1 Sukadana Baru. A descriptive qualitative method with a case study approach was employed. Research subjects included the principal, teachers, and students in grades IV-VI. Data collection techniques included participant observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model (reduction, display, conclusion). Data validity was ensured through source triangulation, technique triangulation, member checking, and extended participation. The results showed: (1) The implementation of infaq and shodaqoh habituation was carried out routinely, voluntarily, and integrated into the school culture; (2) Character values formed include social concern, empathy, sincerity, responsibility, and sharing habits; (3) Positive impacts were observed in increased concern for peers, empathy, willingness to share, and social responsibility. This study concludes that consistent infaq and shodaqoh habituation, supported by teacher role modeling and a conducive school culture, effectively shapes caring and sharing character in elementary school students.